The Real Face of India : India, Myths and Realities - Chaudhry, Riaz Ahmad (Lahore Riaz Publishers, 2011)
Critical study of Indian foreign policy towards Pakistan.
Include Illustrations, Note and References.
Keywords: India -- Foreign relations -- Pakistan -- Pakistan -- Foreign relations -- India -- India -- Foreign relations -- 20th century